Comparative age and growth of juvenile dusky kob (Argyrosomus japonicus) in three South African estuaries, with notes on diet and temperature effects - Mafwila, Samuel Kakambi. (Department of Biological Sciences, 2014)
Bibliography: leaves 36-43.